Decomposição de coque, resíduo de vácuo e petróleo extrapesado por piroidrólise para a determinação de cloro - Antes, Fabiane Goldschmidt (2007)
In this work, a method for chlorine determination in petroleum coke, vacuum and atmospheric residues and heavy petroleum was developed. The pyrohydrolysis sample decomposition method was used, which consists of sample pyrolysis at about 1000 oC in presence of water vapor. The influence of the main parameters on the pyrohydrolysis reaction, such as temperature, time of pyrohydrolysis, sample mass, presence of pyrohydrolysis reaction accelerator and chlorine absorption solution were studied. Best precision and accuracy were obtained by heating the sample for 10 min at temperatures in the range of 950 to 1000 oC. The accelerator investigated (V2O5) did not influence on chlorine releasing from the investigated samples. However, the vacuum residue and heavy petroleum samples needed to be partially decomposed prior to the pyrohydrolysis step. This previous decomposition step was carried out in the own pyrohydrolysis reactor. Nitric acid and Mg(NO3)2 were used for that purpose at temperature lower than that of pyrohydrolysis. Chlorine was determined by inductively coupled plasma mass spectrometry using dynamic reaction cell in order to minimize molecular ions interference on chlorine, whereas the 35Cl+ signal was monitored. Good precision (RSD < 8% for petroleum coke and < 12% for the other samples) and accuracy (agreement with certified values and results obtained by other sample decomposition methods) were observed. The limit of quantification was 1.5 mg g-1 of chlorine, while the sample mass was 250 mg and the final volume of the sample solution 20 ml. The sample throughput analysis was 3 h-1. It was concluded the developed method is suitable for the determination of relatively low chlorine concentrations in petroleum coke, vacuum and atmospheric residues and heavy petroleum. Additionally, the method is fast and can be easily used in routine work, while low amount of waste is produced in the laboratory.